-3(7b-5)=99

Simple and best practice solution for -3(7b-5)=99 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(7b-5)=99 equation:


Simplifying
-3(7b + -5) = 99

Reorder the terms:
-3(-5 + 7b) = 99
(-5 * -3 + 7b * -3) = 99
(15 + -21b) = 99

Solving
15 + -21b = 99

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -21b = 99 + -15

Combine like terms: 15 + -15 = 0
0 + -21b = 99 + -15
-21b = 99 + -15

Combine like terms: 99 + -15 = 84
-21b = 84

Divide each side by '-21'.
b = -4

Simplifying
b = -4

See similar equations:

| 1/2,-2,1 | | -34=4a-2a | | h-3.5=7.6 | | h^2=49 | | 5x^2+13x+12=x+5 | | -2(11-9x)-2(x-1)=11x | | 6=5(x)+24 | | cy+fy=j | | h^2=4i | | 3*y-10=y | | 18/b=6 | | 6=(15/2)x | | 1.95x+2.50=27.46 | | -8w+3=-29 | | y=1500(4)-.15 | | h=-16t^2+10t+25 | | 2p-6=8+5(1p+9) | | 2x^2=3x-12 | | y=1500x-.15 | | 250+2.8x= | | 2x^2-8x=-3x+7 | | 2x-6=-6x-2 | | (-2)+2= | | p^2+64+16p=0 | | 7y+5+(3y)= | | 5a-4(a-8)=3+2a | | t*g^2*x-(1)=0 | | -6.5x^2+1.6+24=0 | | (-7)-(-2)= | | 4l^4m^5n^6/5mn= | | y=22-9 | | 4g^2= |

Equations solver categories